PENGGUNAAN APLIKASI PRESMIL UNTUK MENDETEKSI FAKTOR RISIKO KEHAMILAN - Hipni, Rubiati; Zakiah, Zakiah; Daiyah, Isrowiyatun (Media Penelitian dan Pengembangan Kesehatan, 2023)
The need for health knowledge among mothers during the prenatal period is increasing. The research aimed to detect early pregnancy risk factors by developing a PRESMIL application. Mixed methods research with sequential exploratory strategies. Qualitative research with in-depth interviews with 8 experts (1 Obstetrician Specialist, 1 Lecturer in the Department of Nutrition, 2 Health Service Workers, 3 Community Health Center Midwives and 1 IT Personnel) was used to create a questionnaire, determine predisposing factors and risk scores for pregnancy and how to prevent them. Quantitative research to collect data via web applications, as well as risk factor mapping using web-based clustering methods for pregnant women. The total quantitative sample was 41 people, carried out by purposive sampling. The statistical test used to assess the influence between variables is the ANOVA test. There are several factors that influence the risk of pregnancy with a significance level of p<0.005, including Parity (p=0.002), pregnancy spacing (p=0.049), past disease history (p=0.000), and Hb levels (p=0.024) . The PRESMIL application can be used as an alternative tool to detect pregnancy risk. This is shown by the results of research using the PRESMIL application, which shows that the risk of pregnancy is influenced by several factors, including Hb levels, pregnancy spacing, history of previous illnesses, and parity. In addition, the PRESMIL application also provides information and advice regarding preventive steps that can be taken to reduce the risk of pregnancy.